Faktor yang Memengaruhi Penerapan Protokol Kesehatan di Masa Pandemi Covid-19 pada Pengunjung RSUD Tanjung Pura - Muhammad Crystandy; Siregar, Dian Mayasari; Nofalia (PT. PENERBIT TIGA MUTIARA, 2023)
Health development in Indonesia generally aims to increase awareness, ability and willingness to live healthily for every resident in order to achieve the highest level of health, especially during the Covid-19 pandemic. The aim of this research is to determine the influence of knowledge, attitudes and support from health workers on the implementation of health protocols during the Covid-19 pandemic among visitors at Tanjung Pura Hospital, Langkat Regency. The method in this research uses an analytical survey with a cross-sectional approach. The research population was all visitors to Tanjung Pura Regional Hospital in October 2022 with a total sample of 96 people using the Accidental Sampling technique. The data collected was obtained by interviews using a questionnaire. Data analysis used univariate and bivariate analysis. The results of the study showed that knowledge was poor as much as 57.3%, positive attitude was 56.3%, support from health workers was poor as much as 53.1%. The results of bivariate analysis show that the knowledge variable is 0.000, attitude is 0.001, support from health workers is 0.001. So it can be concluded that there is an influence of the variables of knowledge, attitudes and support of health workers on the implementation of health protocols during the Covid-19 pandemic. It is recommended that hospitals implement strict health protocol checks, such as carrying out checks at hospital entrances, making regulations regarding health protocol raids, and imposing sanctions for those who do not comply with health protocols.